Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)7/8*(-5/14)-13/6
=(-5/16)-13/6
=-119/48
b)(-2/3)^2-13/6
=4/9-13/6
=(-31/18)
c)2/3+3/4:(-5/8)
=2/3+(-6/5)
=(-8/15)
a, \(\frac{-3}{7}+\frac{5}{13}-\frac{4}{7}+\frac{8}{13}\)
\(=\frac{-3}{7}-\frac{4}{7}+\frac{5}{13}+\frac{8}{13}\)
\(=-\frac{7}{7}+\frac{13}{13}=-1+1=0\)
b, \(\frac{-5}{14}-\frac{2}{-14}+\frac{1}{8}+\frac{1}{8}\)
\(=\frac{-5}{14}+\frac{2}{14}+\frac{1}{8}+\frac{1}{8}\)
\(=-\frac{3}{14}+\frac{1}{4}=\frac{1}{28}\)
c,\(-\frac{5}{13}-\left(\frac{3}{5}+\frac{3}{13}-\frac{4}{10}\right)\)
\(=-\frac{5}{13}-\frac{3}{13}-\frac{3}{5}+\frac{4}{10}\)
\(=-\frac{8}{13}-\frac{3}{5}+\frac{4}{10}=-\frac{79}{65}+\frac{4}{10}=-\frac{53}{65}\)
d, \(\left[\left(\frac{1}{8}-\frac{9}{7}+\frac{4}{6}-\frac{12}{7}-\frac{1}{2}\right)+\frac{5}{9}\right]\)
\(=\left[\left(\frac{1}{8}-\frac{9}{7}+\frac{2}{3}-\frac{12}{7}-\frac{1}{2}\right)+\frac{5}{9}\right]\)
\(=\left[\left(\frac{1}{8}-\frac{1}{2}-\frac{9}{7}-\frac{12}{7}+\frac{2}{3}\right)+\frac{5}{9}\right]\)
\(=-\frac{65}{24}+\frac{5}{9}=-2\frac{11}{72}\)
a)-3/7+5/13-4/7+8/13
=-3/7-4/7+5/13+8/13
=-7/7+13/13
=-1+1
=0
\(\frac{1+3^4+3^8+3^{12}}{1+3^2+3^4+3^6+3^8+3^{10}+3^{12}+3^{14}}\)
\(=\frac{\left(3^{14}-1\right):\left(3^4-1\right)}{\left(3^{14}-1\right):\left(3^2-1\right)}\)
\(=\frac{3^2-1}{3^4-1}=\frac{9-1}{81-1}=\frac{8}{10}=\frac{1}{10}\)
\(B=\frac{1+3^4+3^8+3^{12}}{1+3^2+3^4+3^6+3^8+3^{10}+3^{12}+3^{14}}\)
\(B=\frac{1+3^4+3^8+3^{12}}{\left(1+3^4+3^8+3^{12}\right)+3^2+3^6+3^{10}+3^{14}}\)
Xét mẫu : \(\left(1+3^4+3^8+3^{12}\right)+3^2\left(1+3^4+3^8+3^{12}\right)=\left(3^2+1\right)\left(1+3^4+3^8+3^{12}\right)\)
Ta có : \(\frac{1+3^4+3^8+3^{12}}{\left(3^2+1\right)\left(1+3^4+3^8+3^{12}\right)}=\frac{1}{3^2+1}=\frac{1}{10}\)
\(A=\frac{1+3^4+3^8+3^{12}}{1+3^2+3^4+3^6+3^8+3^{10}+3^{12}+3^{14}}\)
Ta có :
\(1+3^4+3^8+3^{12}=\left(3^{16}-1\right):\left(3^4-1\right)\)
\(1+3^2+3^4+3^6+3^8+3^{10}+3^{12}+3^{14}=\left(3^{16}-1\right):\left(3^2-1\right)\)
\(\Rightarrow A=\frac{\left(3^{16}-1\right):\left(3^4-1\right)}{\left(3^{16}-1\right):\left(3^2-1\right)}=\frac{3^2-1}{3^4-1}=\frac{1}{10}\)
3 8 + − 14 6 = 9 24 + − 56 24 = 9 + − 56 24 = − 47 24